Nozzle Selection and Adjuvant Impact on the Efficacy of Glyphosate and PPO-Inhibiting Herbicide Tank-Mixtures - Moraes, Jesaelen G. (2021)
PPO-inhibiting herbicides in combination with glyphosate for postemergence applications is a common approach to manage glyphosate- and ALS-inhibitor-resistant weeds. PPO-inhibitors can reduce glyphosate translocation when applied in tank-mixtures, but adjuvants may be used to overcome this effect. Additionally, optimal droplet size may be affected by tank-mixtures of different herbicides and it can be crucial to herbicide efficacy. Field and greenhouse studies were conducted to investigate the impact of nozzle selection and adjuvants on weed control and interactions when applying PPO-inhibitors (fomesafen or lactofen) alone or in tank-mixture with glyphosate to five weed species using six nozzle types. Ultra-coarse droplets were just as effective as medium droplets regardless of the spray solution, but have a lower likelihood of off-target movement. Tank-mixtures applied were consistently antagonistic to common lambsquarters, horseweed, and Palmer amaranth. Only fomesafen was antagonistic to kochia whereas synergistic interactions were observed when glyphosate plus lactofen were applied in combination with COC, DRA + COC, or NIS. Separate applications are advisable with herbicide- and weed-specific situations to avoid antagonism, which is necessary to achieve optimum weed control and maintain the effectiveness of PPO-inhibitors. Future research should continue to look at these important interactions across a wide range of weed species.